The system of indicators of estimation the economic efficiency in the production of goat milk - Rodica Chetroiu; Ion Călin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The analysis of economic efficiency is the main method of economic systems analysis. This concept is the most important qualitative indicator of the economic development, essential factor in accelerating the economic growth and is also one of the criteria for scientific substantiation of decisions. Applied in the milk production domain, represents the obtaining of maximum quantity of milk per animal, with minimal expenditure of manpower and materials. Regarding determining the economic efficiency of goat milk production, the most used indicators are: total physical production, average production, value of total production (total revenue), production costs, material costs, cost per unit, profit, rate of return, breakeven point etc. The paper presents the calculation method of indicators and their average values for 2014.
Keywords: 330; economic efficiency; indicators; milk; goat; rate of return